Analisis Faktor-faktor yang Mempengaruhi Pembelian Impulsif pada Pengguna Aplikasi Tiktokshop - Sri Nuryani; Willem Paul Pattiwael; Muhammad Iqbal (Universitas Batanghari Jambi, 2022)
This study aims to determine the factors that influence impulse buying on Tiktok Shop users. The independent variables in this study are Sales Promotion (X1), Positive Emotions (X2), Motivation (X3) and Price Perception (X4). The population in this study are all Tiktok Shop users who live in Dago, Bandung. The research sample amounted to 240 and the sampling technique used purposive sampling. In addition, this research is a quantitative correlation with data analysis using multiple linear regression analysis. The results showed that the variables of Sales Promotion (X1), Positive Emotions (X2), Motivation (X3) and Price Perception (X4) had a positive and significant effect on Impulsive Purchases (Y) either partially or simultaneously.